PAPA‐like syndrome with heterozygous mutation in the MEFV gene. (9th December 2021) - O'Connor, C.; Kiely, L.; Heffron, C.; Ryan, J.; Bennett, M.
Abstract : A patient presented with a history of recurrent pyoderma gangrenosum, arthritis and extensive acne, prompting a genetic workup for PAPA syndrome. An MEFV mutation was identified and a change in therapeutic strategy from anakinra to colchicine was successful. Click https://www.wileyhealthlearning.com/#/online-courses/b52447c0-1d37-472d-b0c0-7817352d6f68 for the corresponding questions to this CME article.